(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The paper presents the theoretical basis for diagnostics and technical condition assessment of reinforced concrete bridges in service. The main groups of defects and damage are classified and their influence on load-carrying capacity is discussed. The review covers non-destructive testing methods, including ultrasonic, vibration-based and radiographic techniques, as well as static and dynamic load testing. Mathematical models for residual life prediction and reliability assessment are summarized, and an algorithmic workflow for bridge diagnostics is proposed. An example of practical application to a 24 m span bridge demonstrates the use of measured concrete strength, crack width, reinforcement loss and deflection data for assigning a condition category and repair decision. The study substantiates the need for an integrated, system-based approach to the evaluation of reinforced concrete bridge structures.